A Practical Laboratory Study Simulating the Lumbar Microdiscectomy: Training Model in Fresh Cadaveric Sheep Spine - Suslu, Hikmet Turan; Tatarli, Necati; Karaaslan, Alp; Demirel, Nail (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Laboratory training models are essential for developing and refining surgical skills prior to clinical application of spinal surgery. A simple simulation model is needed for young residents to learn how to handle instruments and to perform safe lumbar approaches. Our aim is to present a practical laboratory model using a fresh sheep lumbar spine that allows to simulate lumbar microdiscectomy in humans. The material consists of a fresh cadaveric spine from a 2-year-old sheep. The surgical steps for lumbar microdiscectomy were conducted under the magnification of the operating microscope. The cadaveric sheep spine represents a useful model to train posterior lumbar microdiscectomy.
Keywords: laboratory training model; lumbar discectomy; posterior lumbar procedures; sheep spine